Influence of thermocleavable functionality on organic field-effect transistor performance of small molecules - Mahale, Rajashree Y.; Dharmapurikar, Satej S.; Chini, Mrinmoy Kumar; Venugopalan, Vijay (Chemical Physics Letters, 2017)
Diketopyrrolopyrrole based donor-acceptor-donor conjugated small molecules using ethylene dioxythiophene as a donor was synthesized. Electron deficient diketopyrrolopyrrole unit was substituted with thermocleavable (tert-butyl acetate) side chains. The thermal treatment of the molecules at 160 degrees C eliminated the tert-butyl ester group results in the formation of corresponding acid. Optical and theoretical studies revealed that the molecules adopted a change in molecular arrangement after thermolysis. The conjugated small molecules possessed p-channel charge transport characteristics in organic field effect transistors. The charge carrier mobility was increased after thermolysis of tert-butyl ester group to 5.07 x 10(-5) cm(2)/Vs. (C) 2017 Elsevier B.V. All rights reserved.